Impact of the multi-campus system on quality education and service provision: case of MSU Zvishavane. - Kariza, Blessing (Midlands State University, 2017)
The purpose of the study was to establish the impact of the multi-campus system on quality of education and services provided by Midlands State University. MSU has since embarked on an operational system of multiple campuses hence the study sought to understand the possible impact this may have on quality of educated and services provision specifically at the satellite campus with direct comparisons to the institution’s conditions prior the inception of the new campus. The study takes note of how most development efforts that the university makes are partially related to the nation’s development initiatives as well thus the study also shows where it is evident, the attempts(by the institution) to improve quality of education and services while simultaneously addressing the nation’s Zim Asset blue print. To analyze this, the study focuses on three specific Key Result Areas which consist of provision of requisite structures, academic excellence and human capital management and development. The study then proceeds to give conclusions pertaining to each of the research questions before suggesting about 5 recommendations.